Studying 137Cs dynamics during litter decomposition in three forest types in the vicinity of Fukushima Dai-ichi Nuclear Power Plant. Issue 2 (4th March 2018) - Endo, Izuki; Ohashi, Mizue; Tanoi, Keitaro; Kobayashi, Natsuko I.; Hirose, Atsushi; Ohte, Nobuhito
ABSTRACT: To investigate the contribution of soil animals to the cesium-137 ( 137 Cs) concentration change in the course of the litter decomposition process, we conducted litter bag experiments in forest sites located about 50 km northwest from the Fukushima Dai-ichi Nuclear Power Plant. To control the influence of soil animals of different size, two different mesh sizes of litter bags (fine and coarse mesh) were used. Litter bags were placed in three different types of forests: (1) broad-leaved forest, (2) Japanese red pine mixed broad-leaved, and (3) Japanese cedar plantation, for the period from November 2012 to April 2014. Through the whole period, litter was decomposed to 60–70% from the initial dry weight. We found no significant difference between the mesh sizes. The litter 137 Cs concentration and the relative 137 Cs amount in each sampling time from initial 137 Cs amount (relative 137 Cs amount) in broad-leaved and mixed broad-leaved forests increased from the initial. In both forest types, 137 Cs concentration in coarse mesh showed higher than the fine mesh. In cedar plantation, relative 137 Cs amount in both mesh sizes did not differ from the initial value. We assumed that enhancement of the activity of microbes by the mesofauna contributed to an increase in the amount of 137 Cs in the litter. Although we could not deny the effect of mesh size of the litter bag, the activity of soil organism could be one of the factors that lead to an incremental increase of the 137 Cs amount in the litter layer.